Metaphor in Cognitive Approach - Połowniak-Wawrzonek, Dorota (Respectus Philologicus, 2014)
The article presents issues relevant to the cognitive theory of metaphor developed by G. Lakoff and M. Johnson. The researchers suggest that metaphors are common. They are rooted in the experience, important in the perception of the world, thinking, acting, as revealed in the language. The metaphor of language is a reflection of a conceptual metaphor. Lakoff and Johnson point out that the metaphor of language occurs in the texts of various types, from the colloquial language to the specialist language. A metaphor carries out two important functions: explaining and facilitating understanding. It enables a partial understanding of some kind of experience in terms of another type of beings and experiences. Some issues such as the concept of love, metaphysical issues, become possible to understand only through metaphor. Thus, the thesis, which treats about necessity of metaphor, is significant. In the process of metaphorical cognition, there is a projection, which takes the source domain to the target domain. A thesis about invariant is important here. Metaphorical mapping is partial. At the root metaphor is structural similarity between domains or their correlations in our experience. Conceptual metaphors can create complex structural relationships. In the case of metaphor the thesis of one-way metaphorical mappings is as important as the thesis about her creative potential. Prominent semantics of conceptual metaphor cannot give full meaning in the literal paraphrase. Among the conceptual metaphors structural metaphors, orientation and ontological metaphors are characterized.
Keywords: cognitivism; metaphor